Reactive fragments targeting carboxylate residues employing direct to biology, high-throughput chemistry. Issue 4 (22nd February 2023) - Thomas, Ross P.; Grant, Emma K.; Dickinson, Eleanor R.; Zappacosta, Francesca; Edwards, Lee J.; Hann, Michael M.; House, David; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract : We present a carboxylate-targeting reactive fragment screening platform using 2-aryl-5-carboxytetrazole (ACT) as the photoreactive functionality. This work will provide a simple accessible method to rapidly discover tool molecules to interrogate important biological targets. Abstract : The screening of covalent or 'reactive' fragment libraries against proteins is becoming an integral approach in hit identification, enabling the development of targeted covalent inhibitors and tools. To date, reactive fragment screening has been limited to targeting cysteine residues, thus restricting applicability across the proteome. Carboxylate residues present a unique opportunity to expand the accessible residues due to high proteome occurrence (∼12%). Herein, we present the development of a carboxylate-targeting reactive fragment screening platform utilising 2-aryl-5-carboxytetrazole (ACT) as the photoreactive functionality. The utility of ACT photoreactive fragments (ACT-PhABits) was evaluated by screening a 546-membered library with a small panel of purified proteins. Hits identified for BCL6 and KRAS G12D were characterised by LC-MS/MS studies, revealing the selectivity of the ACT group. Finally, a photosensitised approach to ACT activation was developed, obviating the need for high energy UV-B light.